IDENTIFIKASI SOCIAL ENGAGEMENT BERDASARKAN LINGKUNGAN TEMPAT TINGGAL DAN PENGARUHNYA TERHADAP FUNGSI KOGNITIF LANSIA DI POSYANDU LANJUT USIA KERTAPATI PALEMBANG TAHUN 2015 - Faiza Yuniati; Serli Shobur (Poltekkes Kemenkes Jambi, 2016)
One common cognitive impairment experienced by the elderly are forgetfulness. This isa sign of decline in cognitive abilities get worse for the foreseeable future if not administeredproperly. One of the causes of cognitive impairment is elderly social support (socialengagement). Social support is very important in the life of the elderly who live in a community.Increased social lifestyle associated with higher cognitive value to the community as a socialactivity presents the challenge of effective communication and participation in interpersonalrelationships.This study aims to identify the social engagement of elderly, both social activities,spiritual, art, culture, relationships with family, the fulfillment of family economic, socialnetworks, membership in the community and others based on the neighborhood in three groupsof Posyandu Elderly in Kertapati Palembang associated with cognitive function. This researchis a quantitative research with cross sectional study design. This study took a sample of 60elderly people were taken proportionally to the three groups of Posyandu Elderly in KertapatiPalembang considering the inclusion and exclusion criteria. Social activities and social networks of the elderly in Posyandu Elderly Kertapatiassociated with cognitive functions of the elderly. Elderly people who have social activities andsocial networks that are less good at risk of impaired cognitive function